Logging mats and logging residue as ground protection during forwarder traffic along till hillslopes - Ring, Eva (Array, 2021)
Forest soils in Northern Europe are generally trafficked by forest machinery on several occasions during a forest rotation. This may create ruts (wheel tracks), which could increase sediment transport to nearby surface water, reduce recreational value, and affect tree growth. It is therefore important to reduce soil disturbance during off-road forest transportation. In this study, rut depth was measured following forwarder traffic on study plots located along four harvested till hillslopes in Northern Sweden with drier soil conditions uphill and wet conditions downhill. The treatments included driving 1) using no ground protection, 2) on logging residue (on average, 38–50 kg m–2) and 3) on logging mats measuring 5×1×0.2 m. The hillslopes contain areas with a high content of boulders, stones, and gravel as well as areas with a significant content of silt. Six passes with a laden forwarder with four bogie tracks were performed. On the plots with ground protection, the application of logging residue and the application and removal of logging mats necessitated additional passes. Rut depth was measured using two methods: 1) as the difference in elevation between the interpolated original soil surface and the surface of the rut using GNSS positioning (Global Navigation Satellite Systems), and 2) manually with a folding rule from an aluminium profile, placed across the rut, to the bottom of the rut. The two methods generally gave similar results. Driving without ground protection in the upper part of the hillslopes generated ruts with depths.